Rural out-migration in the drought prone areas of Ethiopia: A multilevel analysis - Ezra, M.; Kiros, G. e.
tbls.
pp. 749-771
Keywords: Migración; Etiopia; Zonas Rurales; Analisis Multivariado; Siglo XX